2018
DOI: 10.1007/s13197-018-3432-3
|View full text |Cite
|
Sign up to set email alerts
|

Rheology, acceptability and texture of wheat flour tortillas supplemented with soybean residue

Abstract: Dry soybean (Glycine max) residue (SBR) is a byproduct rich in dietary fibre and protein with high levels of essential amino acids. The effects due to the substitution of refined wheat flour with 5% or 10% SBR in dough rheology and hot-press tortilla texture, dimensions, colour, protein and dietary fibre contents were studied. Substitution of 10% SBR improved flour in terms of gluten strength and sedimentation without significantly affecting dough hardness, cohesiveness, adhesiveness, and extensibility. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…In this same sense, a cookie with grape pomace also increased the aroma, appearance and acceptability keeping the rest of the attributes the same and increasing the BCs (Maner et al, 2017). Similar results were observed for a rice cracker enriched with apple pomace (Mir et al, 2017).…”
Section: By-productsupporting
confidence: 75%
See 4 more Smart Citations
“…In this same sense, a cookie with grape pomace also increased the aroma, appearance and acceptability keeping the rest of the attributes the same and increasing the BCs (Maner et al, 2017). Similar results were observed for a rice cracker enriched with apple pomace (Mir et al, 2017).…”
Section: By-productsupporting
confidence: 75%
“…In this same sense, a cookie enriched with grape pomace also increased the aroma, appearance and acceptability while keeping the rest of the attributes the same but increasing the BCs (Maner et al, 2017). Similar results were observed for a rice cracker fortified with apple pomace (Mir et al, 2017). Studies have reported that the addition of by-products to bread modifies the textural properties mainly by the increasing PCs and DF, which may interact with the dough preventing the formation of gluten ramification (Mildner-Szkudlarz et al, 2015;Smith & Yu, 2015).…”
Section: Use Of Agro-industrial By-products In Bakery Productssupporting
confidence: 74%
See 3 more Smart Citations